Expression, function and clinical application of stanniocalcin‐1 in cancer - Zhao, Fangyu (J Cell Mol Med, 2020)
The glycoprotein stanniocalcin‐1 functions as a regulatory endocrine hormone that maintains the balance of calcium and phosphorus in bony fish and as a paracrine/autocrine factor involved in many physiological/pathological processes in humans, including carcinogenesis. In this review, we provide an overview of (a) the possible mechanisms through which STC1 affects the malignant properties of cancer, (b) transcriptional and post‐transcriptional regulation pathways of STC1 and (c) the potential clinical relevance of STC1 as a cancer biomarker and even a therapeutic target in the future. Exploring the role of STC1 in cancer development may provide a better understanding of the tumorigenesis process in humans and may facilitate finding an effective therapeutic method against cancer.